Lifelong Learning from a British Political Perspective: The Case of the University for Industry - AZOUI, Samih (Journal of Human Sciences, 2015)
This article purports to account for the British government’s resort to sell Ufi ltd to a private group of investors in 2011—after more than a decade of strenuous official efforts (both political and financial) to make of it a higher education success story. The central argument is that New Labour politicians’ superficial interpretation of the concept of lifelong learning, due to their tight market-economy party-political agenda, has caused the failure of most of their higher education reforms. This state of affairs forced some concerned academics to react.